Combination of Corn Waste and Egg Shell as Zn Metal Adsorbent with Batch System - Ulfa Imroathul Hasanah; Budi Utami; Endang Susilowati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
This study aims to determine: the ability of corn cobs and eggshells as Zn metal adsorbents, functional groups of corn cobs and eggshells adsorbent, what isotherm patterns occur in the adsorbent corn cobs and eggshells in adsorbing Zn metal, the optimum ratio and optimum mass of the adsorbent composition of corn cobs and eggshells in Zn metal adsorption, the optimum contact time for adsorbent corn cobs and eggshell in adsorbing Zn metal, the optimum concentration of adsorbate to be adsorbed by corn cobs and eggshell adsorbents. This study used an experimental method in the laboratory. characterization includes functional groups using FTIR, and test the effectiveness of adsorbents using the AAS instrument. Kinetic analysis of adsorbent by adsorption isotherm with Langmuir isotherm, Freundlich isotherm, Temkin isotherm, and dubinin-radushkevivh isotherm. The results showed that: Corn cobs and eggshells can be used as zinc metal adsorbents; in the corn cobs adsorbent, there is a functional group -OH at wave number 3415,15 cm-1 and in the eggshell, there is a bent vibration of calcium carbonate at wave number 3400,65 cm-1, the adsorption process of Zn metal by adsorbent corn cobs and egg shells follows the Langmuir isotherm pattern (chemical adsorption), the comparison of the optimum composition and mass of the adsorbent corn cobs and eggshells in Zn metal adsorption are 1:2 and 0,15 grams with Zn metal adsorbed by 80,4571%, the optimum contact time for the adsorbent corn cobs and eggshells in adsorbing Zn metal is 90 minutes with the percentage of absorbed Zn metal concentration is 75,5957%, and the optimum concentration of adsorbate for adsorbed by corn cob and eggshell adsorbents is 1 mg/L with adsorbed Zn percentage of 82,8377%.